Testing for monogenic diabetes is lower than required to reveal its true prevalence in an Australian population - Aleena S. Ali; Jay C.S. Wong; Ainsley Campbell; Elif I. Ekinci (Diabetes Epidemiology and Management, 2022)
Aims: Monogenic diabetes is responsible for 1–5% of all cases of diabetes. A previous Australian study estimated a prevalence of 89 cases per million adults, or one in 280 people with diabetes. Approximately 80% of monogenic diabetes is misdiagnosed as type 1 or type 2 diabetes. Our aims were: 1. To estimate the incidence of referral for genetic testing for monogenic diabetes at an Australian tertiary hospital. 2. To estimate the proportion of individuals with confirmed monogenic diabetes out of those who are referred for genetic testing. 3. To investigate the clinical, biochemical and genetic characteristics of patients with confirmed monogenic diabetes in an Australian population. Methods: We conducted a retrospective audit of patients referred to the genetics service at Austin Health for testing for monogenic diabetes from August 2018 to January 2021, inclusive. We collected pre-existing clinical, biochemical and genetic data from electronic medical records from patients with both confirmed and suspected monogenic diabetes. Results: Of approximately 2576 referrals to the diabetes clinic at Austin Health between December 2018 and January 2021, 46 individuals (1.8%, 95% CI 1.3–2.3%) were referred for genetic testing. Of the individuals referred for testing, 16 (35%, 95% CI 23-49%) declined testing and 3 (6.5%, 95% CI 2.2–18%) did not proceed with genetic testing due to their clinician identifying this as low-yield. Of the 27 individuals who were tested, ten individuals had a positive genetic test result (37%, 95% CI 22-58%) and 1 (2.1%, 95% CI 0.38–11%) had a variant of uncertain significance. GCK variants were the most common variant detected. Conclusion: Approximately 0.39% (95% CI 0.21–0.71) of people seen in the diabetes clinics at a tertiary centre were diagnosed with monogenic diabetes over a period of 26 months.